Treatment outcomes of prostate cancer patients with Gleason score 8-10 treated with definitive radiotherapy - ALSAN ÇETİN, İLKNUR (SPRINGER HEIDELBERG, 2019)
Purpose To validate the clinical outcomes and prognostic factors in prostate cancer (PCa) patients with Gleason score (GS) 8-10 disease treated with external beam radiotherapy (EBRT)+ androgen deprivation therapy (ADT) in the modern era. Methods Institutional databases of biopsy proven 641 patients with GS 8-10 PCa treated between 2000 and 2015 were collected from 11 institutions. In this multi-institutional Turkish Radiation Oncology Group study, a standard database sheet was sent to each institution for patient enrollment. The inclusion criteria were, T1-T3N0M0 disease according to AJCC (American Joint Committee on Cancer) 2010 Staging System, no prior diagnosis of malignancy, at least 70Gy total irradiation dose to prostate +/- seminal vesicles delivered with either three-dimensional conformal RT or intensity-modulated RT and patients receiving ADT. Results The median follow-up time was 5.9 years (range 0.4-18.2 years); 5-year overall survival (OS), biochemical relapse-free survival (BRFS) and distant metastases-free survival (DMFS) rates were 88%, 78%, and 79%, respectively. Higher RT doses (>= 78Gy) and longer ADT duration (>= 2 years) were significant predictors for improved DMFS, whereas advanced stage was a negative prognosticator for DMFS in patients with GS 9-10. Conclusions Our results validated the fact that oncologic outcomes after radical EBRT significantly differ in men with GS 8 versus those with GS 9-10 prostate cancer. We found that EBRT dose was important predictive factor regardless of ADT period. Patients receiving 'non-optimal treatment' (RT doses <78Gy and ADT period <2 years) had the worst treatment outcomes.
Keywords: Pelvic radiotherapy; Grading system; Intensity modulated radiation therapy; Hormonal treatment; Androgen deprivation therapy; EXTERNAL-BEAM RADIOTHERAPY; PHASE-III TRIAL; DOSE-ESCALATION TRIAL; RADICAL PROSTATECTOMY; RADIATION-THERAPY; ANDROGEN SUPPRESSION; BRACHYTHERAPY BOOST; GROUPING SYSTEM; SHORT-TERM; VALIDATION